COVID-19 and Digital Financial Inclusion in Africa : How to Leverage Digital Technologies During the Pandemic - Machasio, Immaculate Nafula (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) pandemic and resulting containment measures are likely to cause an economic contraction of about 2.8 percent in Sub-Saharan Africa (SSA) in 2020 according to the Global Economic Prospects. Among the many adverse effects in the global economy, the crisis is posing a deep threat to financial inclusion efforts globally. Lockdowns and curfews designed to curb the spread of the virus resulted in the closure of bank branches and halted operations of mobile money agents in compliance with restrictions. Government officials and health practitioners encouraged use of cashless and contactless modes of payment to reduce the risk of virus spread through handling of cash, thus creating new opportunities for potential adoption of Digital Financial Services (DFS). Small firms and low-income households can directly benefit from digital solutions such as mobile money services, online banking and other financial technology innovations. Recent evidence suggests that digital financial inclusion could significantly contribute to economic growth, reduce poverty and narrow income inequalities without necessarily causing adverse effects on financial stability given the appropriate regulatory framework. The brief focuses on the impact of COVID-19 on financial inclusion and the potential of robust policy responses. The authors drew on the Global Findex database to showcase policy options that harness maximum benefits from digital technology, promoting financial inclusion and mitigating adverse impacts during the pandemic and beyond. The poor and vulnerable groups, such as women, the rural poor and youth, are bearing the economic brunt of the socioeconomic consequences of the pandemic. Day laborers and those in the informal sector are also among the most affected categories of workers.